HUBUNGAN UKURAN ANTROPOMETRI DENGAN DERAJAT OBSTRUCTIVE SLEEP APNEA - Tori, Marthin; Suryawati, Herlina; Husni, Amin (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
CORRELATION BETWEEN ANTHROPOMETRIC MEASUREMENTS AND STAGE OF OBSTRUCTIVE SLEEP APNEAABSTRACKIntroduction: Obstructive sleep apnea (OSA) is estimated to occur 2-10% worldwide and associated with various diseases. OSA severity can be assessed by apnea hypopnea index (AHI). Increased anthropometric measurements indicate increased thickness of fatty tissue in the neck, as well as fatty deposits of the abdomen which can cause constriction of the airways. Other variables suspected to have an effect on AHI are age, sex, smoking habit, and Mallampati score.Aims: To analyze the correlation between anthropometric measurements and OSA severity.Methods: Descriptive analytic studies on OSA patients treated at Dr. Kariadi Hospital, Semarang, January- August 2017. Subjects were included in the study if STOPBANG score was >2. Anthropometric measurements (body mass index, neck circumference, abdominal circumference) was performed on the basis of the International Organization for Standardization (ISO) method while AHI was measured with polysomnography.Results: Bivariate correlation test on 23 subjects showed significant correlation between OSA severity with body mass index (BMI) and neck circumference but no significant correlation with abdominal circumference. Multivariate test showed the most influential variable was BMI.Discussion: There were significant correlations between anthropometric measurements (BMI and neck circumference) with OSA severity.Keywords: Abdominal circumference, apnea hypopnea index, body mass index, neck circumference, obstructive sleep apneaABSTRAKPendahuluan: Obstructive sleep apnea (OSA) diperkirakan terjadi 2-10% di seluruh dunia yang berkaitan dengan berbagai macam penyakit. Derajat OSA dinilai dengan indeks apnea-hypopnea (apnea hypopnea index/AHI). Tingginya nilai antropometri tubuh menandakan tebalnya jaringan lemak pada leher, demikian pula deposit lemak pada abdomen dapat menyebabkan penyempitan pada saluran napas. Variabel lain yang diduga berpengaruh terhadap AHI adalah usia, jenis kelamin, kebiasaan merokok, dan skor Mallampati.Tujuan: Menganalisis hubungan ukuran antropometri dengan derajat OSA.Metode: Studi deskriptif analitik secara potong lintang dilakukan terhadap pasien dengan OSA di RSUP Dr. Kariadi, Semarang, pada bulan Januari-Agustus 2017. Kriteria inklusi adalah pasien yang dicurigai OSA berdasarkan skor STOPBANG >2. Pemeriksaan antropometri (indeks massa tubuh/IMT, lingkar leher, dan lingkar perut) berdasarkan metode dari ISO (the International Organization for Standardization), sedangkan pemeriksaan AHI menggunakan polisomnografi.Hasil: Uji korelasi bivariat terhadap 23 subjek menunjukkan hubungan bermakna antara derajat OSA dengan IMT dan lingkar leher, namun tidak berhubungan dengan lingkar perut. Uji multivariat menunjukkan variabel yang paling berhubungan dengan derajat OSA adalah IMT.Diskusi: Terdapat hubungan bermakna antara ukuran antropometri (IMT dan lingkar leher) dengan derajat OSA.Kata kunci: Apnea hypopnea index, indeks massa tubuh, lingkar leher, lingkar perut, obstructive sleep apnea